Silicon carbide powder and method for producing the same

By producing silicon carbide powder with high average sphericality and controlled particle size, the challenges of agglomeration and insufficient insulation in conventional powders are addressed, resulting in improved heat dissipation and electrical insulation properties.

JP2025059652APending Publication Date: 2025-04-10MITSUI MINING & SMELTING CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023169883
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-29
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

Conventional silicon carbide powders with small particle sizes tend to agglomerate, leading to insufficient heat dissipation and electrical insulation properties.

Method used

A silicon carbide powder with an average sphericality of 0.70 or higher and a particle size range of 0.40 μm to 3.70 μm, produced using a method involving a laminar plasma frame and controlled plasma output ratio, to enhance particle contact and distribution.

Benefits of technology

The resulting silicon carbide powder exhibits improved heat dissipation and electrical insulation properties, with enhanced flowability and sinterability, making it suitable for advanced heat dissipation materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025059652000001_ABST
    Figure 2025059652000001_ABST
Patent Text Reader

Abstract

To provide a silicon carbide powder having improved heat dissipation properties and electrical insulation properties compared to conventional powders, and to provide a method for easily producing the silicon carbide powder having improved heat dissipation properties and electrical insulation properties compared to conventional powders.SOLUTION: A silicon carbide powder is an aggregate of silicon carbide particles. An average sphericity of the silicon carbide powder is 0.70 or more. The silicon carbide powder has a volume cumulative particle size D50 at 50 vol.% by cumulative volume, as measured by laser diffraction particle size distribution analysis, of 0.40 μm or more and 3.70 μm or less. It is preferable that the silicon carbide particles comprise particles having a β-type crystal structure. It is also preferable that the silicon carbide powder contains 38 mass% or more of the silicon carbide particles having the β-type crystal structure.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to silicon carbide powder and a method for producing the same. [Background technology]

[0002] In recent years, electronic components have become smaller and more integrated, and are increasingly powerful. Since such electronic components generate a large amount of heat during operation, the materials that make up the electronic components are required to have further improved heat dissipation and electrical insulation. Thermally conductive particles with excellent insulation properties are desired as materials that have heat dissipation and electrical insulation properties.

[0003] For example, Patent Document 1 describes a resin composite material in which the surface of conductive ultrafine powder made of a carbon material is coated with silicon dioxide or the like. According to the document, the resin composite material is produced by the following method. First, carbon black and tetraethoxysilicate, a coupling agent, are added to isopropanol, then distilled water is added dropwise, and N,N-dimethylacetamide is further added dropwise to replace the solvent. After that, phenyltrimethoxysilane is added to the solvent and heated, and the solvent is filtered and dried, and the resin composite material is produced by baking at 350°C for 30 minutes in a nitrogen atmosphere. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2010-24406 A Summary of the Invention [Problem to be solved by the invention]

[0005] The particles obtained by the technique described in Patent Document 1 have a small particle size of 1 nm or more and 500 nm or less, and therefore tend to aggregate with each other. For this reason, it is not easy for the particles to exhibit sufficient heat dissipation and electrical insulation properties for practical use. Therefore, an object of the present invention is to provide a material having improved heat dissipation and electrical insulation properties compared to conventional materials. [Means for solving the problem]

[0006] The present invention relates to a silicon carbide powder which is an aggregate of silicon carbide particles, The average sphericity is 0.70 or more, Volume cumulative particle size D at 50% cumulative volume measured by laser diffraction scattering particle size distribution measurement method 50 The above-mentioned problems are solved by providing a silicon carbide powder having a particle size of 0.40 μm or more and 3.70 μm or less.

[0007] The present invention also provides a method for producing silicon carbide powder, comprising the steps of supplying mother powder containing silicon carbide into a plasma flame in a laminar flow state generated in a chamber, gasifying the mother powder in the plasma flame, and cooling the gasified mother powder to generate silicon carbide particles, The present invention provides a method for producing silicon carbide powder, in which the ratio of plasma output to the supply amount of base powder is 0.003 kW·min / g or more and 20 kW·min / g or less. Effect of the Invention

[0008] According to the present invention, it is possible to provide silicon carbide powder having improved heat dissipation and electrical insulation properties compared to conventional ones. Furthermore, according to the present invention, it is possible to easily produce silicon carbide powder having improved heat dissipation and electrical insulation properties compared to conventional ones. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic diagram showing an example of a DC plasma device capable of suitably producing the silicon carbide powder of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention will be described below based on its preferred embodiments. The present invention relates to a silicon carbide powder. The silicon carbide powder is composed of an aggregate of silicon carbide particles. The silicon carbide particles mainly contain carbon (C) and silicon (Si), and these elements are mainly present in the particles as silicon carbide (SiC). The silicon carbide powder of the present invention is substantially composed of silicon carbide particles, but is allowed to contain unavoidable impurities. When the silicon carbide powder contains unavoidable impurities, the content of the unavoidable impurities is preferably 0.01 mass% or less, since the inherent properties of the silicon carbide powder are not easily impaired. The presence or absence of unavoidable impurities and the content of the unavoidable impurities can be measured, for example, by ICP emission spectroscopy.

[0011] One of the characteristics of silicon carbide powder is its shape. Specifically, the average sphericity of silicon carbide powder is preferably 0.70 or more. The average sphericity is an index representing the degree of sphericity of silicon carbide powder, and the larger this value, the closer the shape of the silicon carbide powder is to a perfect sphere. Silicon carbide is generally known to be a very hard compound. As a result, in silicon carbide powder, even if the silicon carbide particles constituting the powder collide with each other, the particles are unlikely to deform. As a result, in conventional silicon carbide powder, the contact between the particles becomes point contact, and it is difficult to obtain a sufficient number of contact points. Furthermore, when particles are produced by a breakdown method such as pulverization, the shape becomes indefinite, which causes the contact between the particles to be random. For these reasons, it has been difficult to utilize the excellent properties of silicon carbide, such as heat dissipation (heat transfer). In contrast, since the silicon carbide powder of the present invention has an average sphericity of a predetermined value or more, it is expected that the contact between the particles will be regular, and that the contact frequency and contact area between the particles will be large. Therefore, according to the silicon carbide powder of the present invention, the excellent heat dissipation and electrical insulation inherent to silicon carbide can be utilized more easily than before, and these properties are improved. For this reason, the average sphericity of the silicon carbide powder is more preferably 0.80 or more, and even more preferably 0.85 or more. The higher the average sphericity of the silicon carbide powder, the more preferable it is.

[0012] In order to make the average sphericity of the silicon carbide powder equal to or greater than the above value, it is preferable to adjust the plasma flame so that it is in a laminar flow state and long in the production method described below, or to adjust the plasma output.

[0013] The silicon carbide powder preferably contains a predetermined amount of silicon carbide powder having a sphericity of 0.85 or more. Specifically, the silicon carbide powder preferably contains 50% by number, more preferably 55% by number, and even more preferably 60% by number of silicon carbide powder having a sphericity of 0.85 or more. The more the amount of silicon carbide powder having a sphericity of 0.85 or more, the more preferable it is, but if it is about 70% by number, the desired effect is sufficiently achieved.

[0014] The average sphericity of silicon carbide powder is calculated, for example, based on observation with a scanning electron microscope (SEM). Specifically, first, silicon carbide powder attached to a cotton swab is dropped from above onto an SEM sample stage with carbon tape attached. Then, excess silicon carbide powder is removed with an air gun to obtain an observation sample. The conditions for spraying with the air gun include, but are not limited to, spraying air at 5 atmospheres (gauge pressure) for 1 second from a position 10 cm away. SEM observation is preferably performed at an acceleration voltage of 5 kV to 15 kV and an observation magnification of 40 times to 1000 times. The average sphericity is determined by observing SEM images of 50 arbitrary silicon carbide particles and calculating the average sphericity based on the following formula (1). In formula (1), S is the area of ​​the silicon carbide particle calculated from the SEM image, and L is the perimeter of the particle. Sphericity=4πS / L 2 (1)

[0015] Silicon carbide powder is measured by a laser diffraction scattering particle size distribution measurement method, and the cumulative particle size D at 50% cumulative volume is 50(Hereinafter, simply "particle size D 50 It is also preferable that the flowability of the silicon carbide powder is improved, so that when a heat dissipation material is produced using the silicon carbide powder and a resin, the powder is easily distributed throughout the resin, improving the heat dissipation and electrical insulation of the heat dissipation material. For this reason, silicon carbide powders are made with a particle size of D 50 For the same reason, the silicon carbide powder has a particle size D of preferably 0.40 μm or more, more preferably 0.46 μm or more, and even more preferably 0.60 μm or more. 50 However, it is preferably 3.70 μm or less, more preferably 3.40 μm or less, and even more preferably 3.10 μm or less.

[0016] In order to make the above-mentioned effect of improving the heat dissipation and electrical insulation of the heat dissipation material more pronounced, the silicon carbide powder is 10 (Hereinafter, simply "particle size D 10 It is also preferable that the particle size D is within a certain range. 10 From the same viewpoint, the silicon carbide powder has a particle size D of preferably 0.19 μm or more, more preferably 0.24 μm or more, and even more preferably 0.27 μm or more. 10 However, it is preferably 1.30 μm or less, more preferably 1.20 μm or less, and even more preferably 1.00 μm or less.

[0017] In order to make the above-mentioned effect of improving the heat dissipation and electrical insulation of the heat dissipation material more pronounced, the silicon carbide powder is 90 (Hereinafter, simply "particle size D 90 It is also preferable that the particle size D is within a certain range. 90From the same viewpoint, the silicon carbide powder has a particle size D of preferably 1.10 μm or more, more preferably 1.60 μm or more, and even more preferably 1.80 μm or more. 90 However, it is preferably 11.00 μm or less, more preferably 9.80 μm or less, and even more preferably 8.90 μm or less.

[0018] Silicon carbide powder particle size D 50 In order to keep the above range, it is preferable to adjust the ratio of plasma output to the supply amount of mother powder within a predetermined range or adjust the length of the plasma flame in the production method described below.

[0019] It is also preferable that the silicon carbide powder has a standard deviation SD of its particle size distribution within a predetermined range, which improves the flowability of the silicon carbide powder and, for example, improves the heat dissipation and electrical insulation of a heat dissipation material produced by using the silicon carbide powder and a resin. For this reason, the silicon carbide powder preferably has a standard deviation SD of particle size distribution of 0.28 or more, more preferably has a standard deviation SD of particle size distribution of 0.53 or more, and even more preferably has a standard deviation SD of particle size distribution of 0.55 or more. For the same reason, the silicon carbide powder preferably has a standard deviation SD of particle size distribution of 4.60 or less, more preferably has a standard deviation SD of particle size distribution of 3.40 or less, and even more preferably has a standard deviation SD of particle size distribution of 3.00 or less.

[0020] It is also preferable that the silicon carbide powder has a BET specific surface area within a predetermined range, which improves the flowability of the silicon carbide powder and, for example, improves the heat dissipation and electrical insulation of a heat dissipation material produced by using the silicon carbide powder and a resin. For this reason, silicon carbide powder has a BET specific surface area of ​​4.8 m 2 / g or more, and 7.2m 2 More preferably, it is 8.0m / g or more. 2For the same reason, the silicon carbide powder preferably has a BET specific surface area of ​​25.0 m 2 / g or less, and 17.0m 2 / g or less, and more preferably 14.0m 2 It is even more preferable that the molecular weight is not more than 1 / g.

[0021] The BET specific surface area of ​​silicon carbide powder can be measured by the following method. For example, it can be measured according to "(3.5) One-point method" of "6.2 Flow method" of JIS R1626 "Gas adsorption of fine ceramic powder - Measurement method of specific surface area by BET method" using a nitrogen-helium mixed gas containing 30 volume % nitrogen gas as an adsorption gas and 70 volume % helium gas as a carrier gas and a BET specific surface area measuring device (HM model-1210, manufactured by Mountec Co., Ltd.).

[0022] The silicon carbide particles preferably contain particles having a β-type crystal structure. This makes the silicon carbide powder more easily sintered. In order to make this effect more pronounced, the silicon carbide powder preferably contains 38% by mass or more of silicon carbide particles having a β-type crystal structure, more preferably 40% by mass or more, and even more preferably 42% by mass or more. The more silicon carbide particles having a β-type crystal structure contained in the silicon carbide powder, the more preferable, and 100% by mass is ideal, but the above effect is sufficiently achieved if the silicon carbide powder contains about 98% by mass of silicon carbide particles. The crystal structure being a β type can be determined by observing a diffraction peak in an X-ray diffraction measurement, and by the fact that the diffraction peak has the same position and intensity ratio as the diffraction peak in the database. The amount of silicon carbide particles having a β-type crystal structure contained in the silicon carbide powder is measured, for example, by XRD peak intensity.

[0023] In order to make the silicon carbide particles contain particles having a β-type crystal structure, it is preferable to produce the silicon carbide powder by a direct current thermal plasma method, or to use a physical pulverization method, a laser pyrolysis method, or a plasma CVD method.

[0024] It is also preferable that the silicon carbide powder has a green density within a predetermined range, which improves the packing property of the silicon carbide powder, making it easier to form a good heat conduction path, and further improving the thermal conductivity. For this reason, silicon carbide powder has a green density of 1.60 g / cm 3 It is preferable that the content is 1.80 g / cm or more. 3 For the same reason, the silicon carbide powder preferably has a green density of 2.00 g / cm or more. 3 It is preferable that the density is 1.90 g / cm or less. 3 It is even more preferable that:

[0025] In order to set the green density of the silicon carbide powder within the above range, it is preferable to produce the silicon carbide powder by a direct current thermal plasma method.

[0026] Since silicon carbide is a high-resistance material, the degree of electrical insulation of the silicon carbide powder of the present invention can be evaluated by the compressed volume resistivity of the silicon carbide powder. The higher the compressed volume resistivity, the higher the electrical insulation of the silicon carbide powder. From the viewpoint of further enhancing the electrical insulation of the silicon carbide powder, when the surfaces of the silicon carbide particles are not coated with the high-resistance substance described below, i.e., when the surfaces of the silicon carbide particles are exposed, the pressed volume resistivity under 20 kN is preferably 1.0 Ω cm or more, and more preferably 2.0 Ω cm or more. From the same viewpoint as above, the silicon carbide powder preferably has a pressed volume resistivity of 25.0 Ω cm or more under 20 kN in a state in which the surfaces of the silicon carbide particles are covered with a high resistance material described later, and more preferably has a pressed volume resistivity of 1.0×10 3More preferably, it is 1.0×10 6 It is more preferable that the resistivity is Ω·cm or more. The higher the pressed volume resistivity of silicon carbide powder, the better. However, when the surface of silicon carbide particles is not coated with a high-resistance material, a volume resistivity as high as about 4.5 Ω·cm can be evaluated as being sufficiently high in electrical insulation. For the same reason, when the surface of silicon carbide particles is coated with a high-resistance material, a volume resistivity of 1.0×10 9 If the resistance is high, around Ω·cm, the electrical insulation can be evaluated as being sufficiently high.

[0027] The degree of heat dissipation of the silicon carbide powder of the present invention can be evaluated by the thermal conductivity of the silicon carbide powder. The higher the thermal conductivity, the higher the heat dissipation of the silicon carbide powder. It is preferable that the thermal conductivity of the silicon carbide powder is 1.0 W / m·K or more in thermal conductivity measurement by a steady method in order to further enhance the heat dissipation of the silicon carbide powder. From the viewpoint of making this advantage more prominent, the thermal conductivity in thermal conductivity measurement by a steady method is more preferably 1.2 W / m·K or more, and even more preferably 1.3 W / m·K or more. The higher the thermal conductivity of the silicon carbide powder, the more preferable it is, but if it is about 1.5 W / m·K, it can be evaluated that the heat dissipation is sufficiently high.

[0028] In order to make the pressed volume resistivity and thermal conductivity of the silicon carbide powder equal to or higher than the above values, for example, it is preferable that the surface of the silicon carbide particles is coated with a material having a pressed volume resistivity higher than that of silicon carbide (hereinafter also simply referred to as a "high resistance material"). The term "coating" as used here refers to various states in which a high resistance material is disposed on the surface of a silicon carbide particle, and includes, for example, chemical bonding between silicon carbide constituting the silicon carbide particle and a material other than silicon carbide, and physical adsorption between silicon carbide constituting the silicon carbide particle and a material other than silicon carbide. Examples of high resistance substances include, but are not limited to, various electrical insulating materials and ceramic materials, such as alumina, silicon nitride, and silica. These high resistance substances can be used alone or in combination of two or more. From the viewpoint of more effectively increasing the pressed volume resistivity and thermal conductivity of the silicon carbide powder to the above values ​​or more, it is more preferable that the surface of the silicon carbide particles is coated with alumina, silicon nitride, or silica, and particularly preferable that it is coated with alumina.

[0029] There is no particular limitation on the method for coating the surface of the silicon carbide particles with a high resistance material. However, from the viewpoint of successfully coating the surface with a high resistance material, it is preferable to use a direct current thermal plasma method or a wet coating process, which will be described later.

[0030] The high resistance material may be present so as to cover at least a part of the surface of the silicon carbide particles. Therefore, the high resistance material may cover the entire surface of the silicon carbide particles, or may cover a part of the surface of the particles. The coverage of the high resistance material with respect to the entire surface of the silicon carbide particles is preferably 10% or more, more preferably 30% or more, and even more preferably 50% or more. In addition, the coverage of the high resistance material with respect to the entire surface of the silicon carbide particles is preferably 95% or less. When the coverage of the silicon carbide particles is 30% or more, the electrical insulation of the silicon carbide powder is further improved. When the coverage of the silicon carbide particles is 95% or less, the heat dissipation and electrical insulation of the silicon carbide powder are improved in a well-balanced manner.

[0031] The coverage of silicon carbide particles is measured, for example, by the following method. Specifically, high-resistance materials can be identified and measured by observing silicon carbide particles with a transmission electron microscope (TEM) and measuring them with energy dispersive X-ray analysis (EDS).

[0032] It is also preferred that the surface of the silicon carbide particles coated with a high resistance material is further coated with a dispersant. This further improves the flowability of the silicon carbide powder and the affinity of the silicon carbide powder with resins, etc., so that when a heat dissipation material is produced using the silicon carbide powder and resin, for example, the powder is more easily distributed throughout the resin, and the heat dissipation and electrical insulation of the heat dissipation material are further improved. Examples of the dispersant include, but are not limited to, fatty acids and coupling agents. These dispersants can be used alone or in combination of two or more. The dispersant is appropriately selected depending on the type of highly resistive material that coats the surfaces of the silicon carbide particles.

[0033] The dispersant may be present so as to cover the surface of the silicon carbide particles coated with the high resistance material. Therefore, the dispersant may cover the entire surface of the silicon carbide particles coated with the high resistance material, or may cover a part of the surface of the particles. The coverage of the dispersant with respect to the entire surface of the silicon carbide particles is preferably 10% or more, more preferably 30% or more, and even more preferably 50% or more, from the viewpoint of further improving the fluidity of the silicon carbide powder. From the same viewpoint, the higher the coverage of the dispersant with respect to the entire surface of the silicon carbide particles, the more preferable, but if it is about 95%, the desired effect is sufficiently achieved.

[0034] Next, a preferred method for producing the silicon carbide powder of the present invention will be described. In this method, mother powder containing silicon carbide is subjected to a direct current thermal plasma (hereinafter also referred to as "DC plasma") method to generate silicon carbide particles from the mother powder. In detail, this method includes the steps of supplying the mother powder into a plasma frame in a laminar flow state generated in a chamber, gasifying the mother powder in the plasma frame, and cooling the gasified mother powder to generate silicon carbide particles. When the silicon carbide powder is composed of a single silicon carbide particle, the mother powder may be made of a compound of the single silicon carbide. There is no particular limitation on the method for producing the mother powder.

[0035] A DC plasma device suitable for use in this manufacturing method is shown in FIG. 1. As shown in the figure, the DC plasma device 1 includes a powder supply device 2, a chamber 3, a DC plasma torch 4, a collection pot 5, a powder supply nozzle 6, a gas supply device 7, and a pressure adjustment device 8. In addition, in the DC plasma device 1, a cylindrical body 9 surrounding the plasma flame is arranged in the chamber 3 and directly below the plasma torch 4. The cylindrical body 9 has a longitudinal direction and a width direction perpendicular to the longitudinal direction. The inside of the cylindrical body 9 is hollow. The outer peripheral surface of the cylindrical body 9 and the inner wall of the chamber 3 are connected by a partition plate 10. The partition plate 10 extends radially in the horizontal direction from the outer surface of the cylindrical body 9. Therefore, the inside of the chamber 3 is divided into an upper part and a lower part with the partition plate 10 as a boundary. In this device, the mother powder passes through the inside of the DC plasma torch 4 from the powder supply device 2 through the powder supply nozzle 6. A gas for generating thermal plasma (hereinafter also referred to as "plasma gas") is supplied from a gas supply device 7 to the plasma torch 4 to generate a plasma flame. The mother powder is gasified in the plasma flame generated by the DC plasma torch 4 and released into the chamber 3. The gasified mother powder is then cooled and converted into fine particles of silicon carbide powder 11, which are then accumulated and collected in the collection pot 5. The inside of the chamber 3 is controlled by a pressure regulator 8 to maintain a negative pressure relative to the powder supply nozzle 6, which facilitates the supply of the mother powder to the DC plasma torch 4 and ensures stable generation of the plasma flame. The device shown in FIG. 1 is an example of a DC plasma device, and the production of silicon carbide powder according to the present invention is not limited to this device.

[0036] From the viewpoint of effectively making the average sphericity of the silicon carbide powder equal to or greater than the above value, it is preferable to adjust the length of the plasma flame in a laminar flow state. Specifically, it is preferable to maintain the laminar flow state of the plasma flame for 1.0 cm or more, more preferably for 2.0 cm or more, and even more preferably for 4.0 cm or more. It is also preferable to maintain the laminar flow state of the plasma flame for 25 cm or less, more preferably for 15 cm or less, and even more preferably for 12 cm or less. By maintaining the laminar flow state of the plasma flame within the above range, the temperature of the plasma flame is less likely to drop and is more likely to be uniform, thereby accelerating the generation of silicon carbide particles. Furthermore, the generated silicon carbide particles are less likely to return, and the silicon carbide particles are less likely to become coarse due to collisions between the particles.

[0037] Whether or not the plasma flame is in a laminar flow state can be determined by whether or not the aspect ratio of the frame length to the frame width (hereinafter referred to as the "frame aspect ratio") is equal to or greater than 3 when the plasma flame is observed from the side where the frame width is widest. Specifically, if the frame aspect ratio is 3 or more, it can be determined to be in a laminar flow state, and if it is less than 3, it can be determined to be in a turbulent flow state.

[0038] In order to make the plasma flame longer in a laminar flow state, it is advantageous to adjust the vertical length of the cylindrical body 9. In detail, when the length from the upper end to the lower end of the chamber 3 is the length L1 and the length from the upper end to the lower end of the cylindrical body 9 is the length L2, the value of L2 / L1, which is the ratio of the length L2 to the length L1, is preferably set to 0.10 or more and 0.50 or less, more preferably 0.15 or more and 0.40 or less, and even more preferably 0.20 or more and 0.30 or less. This makes it difficult for heat to dissipate, and promotes the generation of silicon carbide particles. In addition, the temperature of the field where the silicon carbide particles are generated tends to be uniform, which makes it easy to generate silicon carbide particles with a uniform particle size. In addition, the generated silicon carbide particles are less likely to fly back due to the cylindrical body 9 and the partition plate 10, so that collisions between particles are less likely to occur. As a result, particle aggregation is less likely to occur, which also makes it easier to obtain silicon carbide particles with a uniform particle size. From this viewpoint, it is preferable to generate the plasma flame so that the partition plate 10 is located at a position from the upstream side that is 10% to 30%, particularly 10% to 25%, and especially 15% to 20% of the length of the portion of the plasma flame that is in a laminar flow state.

[0039] The laminar flow state of the plasma flame is preferably generated inside the cylindrical body 9. This also makes it difficult for heat to dissipate, promotes the generation of silicon carbide particles, and makes it easier to obtain silicon carbide particles with a uniform particle size. For this reason, when the vertical length of the portion of the plasma flame that is in a laminar flow state is length L3, the value of L3 / L2, which is the ratio of length L3 to length L2, is preferably 0.10 to 0.95, more preferably 0.15 to 0.90, and even more preferably 0.20 to 0.80.

[0040] In order to make the plasma flame long in a laminar flow state, it is also advantageous to adjust the plasma output and plasma gas flow rate. In particular, the plasma output of the DC plasma device is preferably 2.0 kW or more and 100 kW or less, more preferably 10 kW or more and 40 kW or less. The gas flow rate of the plasma gas is preferably 0.10 L / min or more and 25 L / min or less, more preferably 0.5 L / min or more and 21 L / min or less. As the plasma gas, reducing gases such as hydrogen gas, and inert gases such as nitrogen gas and argon gas are preferable.

[0041] Silicon carbide powder particle size D 50 In addition to the viewpoint of keeping the above range, from the viewpoint of making it difficult for coarse-grained mother powder to remain, it is preferable to adjust the ratio of plasma output to the mother powder supply amount within a predetermined range. Specifically, the ratio of plasma output to the mother powder supply amount is preferably 0.003 kW·min / g or more, more preferably 0.1 kW·min / g or more, and even more preferably 0.2 kW·min / g or more. Moreover, the ratio of plasma output to the mother powder supply amount is preferably 20 kW·min / g or less, more preferably 7.0 kW·min / g or less, and even more preferably 4.0 kW·min / g or less. By keeping the ratio of plasma output to the mother powder supply amount within the above range, the total amount of mother powder gasified in the plasma flame increases, and the particle size D 50 This can prevent the particles from colliding with each other, so the particle size D of the silicon carbide powder can be increased. 50 can be within the above range.

[0042] From the viewpoint of reliably obtaining the flow rate required for gasifying the base powder while stably maintaining the plasma flame in a laminar flow state, the ratio of the plasma gas flow rate to the plasma output (unit: L / (min kW)) is set to preferably 0.15 or more and 2.00 or less, more preferably 0.40 or more and 1.70 or less, and even more preferably 0.60 or more and 1.50 or less, while maintaining the plasma output and gas flow rate within the above-mentioned ranges.

[0043] The cylindrical body 9 is a part different from the plasma torch 4 that generates plasma. There are no particular limitations on the cross-sectional shape of the cylindrical body 9. For example, a tube with a circular or rectangular cross section can be used as the cylindrical body 9. From the viewpoint of effectively suppressing a decrease in temperature of the plasma flame, it is preferable that the cylindrical body 9 is a cylinder. In this case, it is preferable that the center position of the cross section of the cylinder and the generation position of the plasma flame roughly coincide with each other from the viewpoint of effectively suppressing a decrease in temperature of the plasma flame.

[0044] When producing silicon carbide particles coated with a high resistance material using the DC plasma device 1 shown in Fig. 1, a mixture of first mother powder containing silicon carbide and second mother powder containing a high resistance material may be used as the mother powder. From the viewpoint of plasma sprayability of the mother powder and cost, the particle size D of the mother powder is set to 100 nm. 50 In both the first mother powder and the second mother powder, the D of the mother powder is preferably 3.0 μm or more and 30 μm or less, and more preferably 5.0 μm or more and 15 μm or less. 50 The measurement of D of silicon carbide powder mentioned above was performed. 50 This can be done in a similar manner to the measurement of

[0045] From the viewpoint of the production efficiency of the obtained silicon carbide powder, the supply rate of the mother powder is preferably 5.0 g / min to 100 g / min, more preferably 10 g / min to 60 g / min, expressed as the total amount of the first mother powder and the second mother powder. Furthermore, with regard to the ratio of the first mother powder to the second mother powder, it is preferable that the second mother powder is contained in an amount of 0.1 mass% to 10 mass% in the total amount of the first mother powder and the second mother powder.

[0046] The shape of the mother powder is not particularly limited in either the first mother powder or the second mother powder, and examples thereof include polyhedral shapes such as dendritic, rod-like, flake-like, and cubic shapes, spherical shapes, and aggregates of one or more shapes. From the viewpoint of stabilizing the supply efficiency to the plasma torch, it is preferable to use mother powder in a polyhedral, spherical, or aggregated shape.

[0047] The first mother powder and the second mother powder preferably have a specific relationship in their melting points. In particular, it is advantageous to use a first mother powder whose melting point is higher than that of the second mother powder. By using a mixed mother powder consisting of the first mother powder and the second mother powder having such a temperature relationship, in the particle generation process, first, the evaporated and vaporized first mother powder is cooled, and nucleation, aggregation, and condensation of silicon carbide, which is the core part, occur, and the core part made of silicon carbide occurs. Next, nucleation, aggregation, and condensation occur due to cooling of the evaporated and vaporized second mother powder (the second mother powder has a lower boiling point than the first mother powder), and the particle is covered with a high resistance material.

[0048] The silicon carbide powder thus obtained may be subjected to post-treatment as necessary. For example, the silicon carbide powder may be dispersed to adjust the particle size distribution of the silicon carbide powder. Dispersion may be performed, for example, by using a mixing device such as a ball mill or a bead mill, or by sieving.

[0049] The silicon carbide powder thus obtained tends to have a spherical shape. In other words, the average sphericity of the silicon carbide powder tends to be equal to or greater than a predetermined value. In addition, the particle diameter D of the silicon carbide powder tends to be equal to or greater than a predetermined value. 50 The standard deviation SD of the particle size distribution and the BET specific surface area tend to fall within the prescribed ranges. Furthermore, the silicon carbide particles tend to have a β-type crystal structure. The silicon carbide particles are preferably used as a raw material for heat dissipation materials, for example, in the form of silicon carbide powder, which is an aggregate of the silicon carbide particles. The heat dissipation materials include the silicon carbide powder of the present invention and a resin. The heat dissipation materials are preferably used, for example, as a heat dissipation material for thermal interphases and a sealing material for power modules.

[0050] Although the present invention has been described based on the preferred embodiment, the present invention is not limited to the above embodiment.

[0051] In relation to the above embodiment, the following silicon carbide powder and a method for producing the same are further disclosed. [1] A silicon carbide powder which is an aggregate of silicon carbide particles, The average sphericity is 0.70 or more, Volume cumulative particle size D at 50% cumulative volume measured by laser diffraction scattering particle size distribution measurement method 50 The silicon carbide powder has a particle size of 0.40 μm or more and 3.70 μm or less.

[0052] [2] The silicon carbide particles include particles having a β-type crystal structure, The silicon carbide powder according to [1], wherein the silicon carbide particles having a β-type crystal structure are contained in the silicon carbide powder in an amount of 38 mass% or more. [3] The surface of the silicon carbide particles is coated with alumina, silicon nitride or silica, The powder volume resistivity under 20 kN is 25.0 Ω cm or more. The silicon carbide powder according to [1] or [2], having a thermal conductivity of 1.0 W / m K or more, as measured by a steady-state thermal conductivity measurement method. [4] The silicon carbide powder according to [3], wherein the surface of the silicon carbide particles coated with alumina, silicon nitride or silica is further coated with a dispersant. [5] A heat dissipation material comprising the silicon carbide powder according to any one of [1] to [4] and a resin. [6] A method for producing silicon carbide powder, comprising the steps of supplying mother powder containing silicon carbide into a plasma flame in a laminar flow state generated in a chamber, gasifying the mother powder in the plasma flame, and cooling the gasified mother powder to generate silicon carbide particles, a ratio of plasma output to the supply amount of the base powder is 0.003 kW·min / g or more and 20 kW·min / g or less. EXAMPLES

[0053] The present invention will be described in more detail below with reference to examples. However, the scope of the present invention is not limited to such examples. Unless otherwise specified, "%" means "% by mass".

[0054] Example 1 Using the DC plasma device shown in FIG. 1, silicon carbide powder was produced by the following method. Silicon carbide-based fine powder (particle diameter: 5 μm, shape: polyhedral) was used as the first mother powder, and this was supplied to the DC plasma device 1. The supply amount of the first mother powder was set to 10 g / min, and the first mother powder was supplied to the DC plasma torch 4 through the powder supply nozzle 6. A mixed gas of nitrogen gas and argon gas was used as the plasma gas. The flow rate of the nitrogen gas was set to 3.5 L / min, and the flow rate of the argon gas was set to 14 L / min. In addition, the plasma output was set to 18 kW so that the laminar flow state of the plasma flame continued for 15 cm. The generated plasma flame was photographed from the side where the frame width was observed to be the widest, and the image was binarized to measure the frame aspect ratio, which is the ratio of the frame length to the frame width. As a result, the frame aspect ratio was 4, and it was confirmed that the plasma flame was in a laminar flow state. In addition, a circular ring was used as the cylindrical body 9. The value of L2 / L1 in the DC plasma device 1 was set to 0.10. The value of L3 / L2 was 0.50. The pressure inside the chamber 3 was set to be negative relative to atmospheric pressure. In addition, during production, nitrogen gas at 25°C was supplied as a cooling gas at a flow rate of 10 L / min. In this manner, the desired silicon carbide powder was obtained. The silicon carbide powder of this example was composed of carbon, silicon, nitrogen, and oxygen elements, as well as unavoidable impurities, and had a SiC content of 90 mass% or more.

[0055] Example 2 In Example 1, the supply amount of the first mother powder was set to 15 g / min. In addition, the plasma output was set to 18 kW so that the laminar flow state of the plasma flame was maintained for 15 cm. Other than this, silicon carbide powder was obtained in the same manner as in Example 1.

[0056] Example 3 In Example 1, the plasma output was set to 21 kW so that the laminar flow state of the plasma flame was maintained for 15 cm. Other than this, silicon carbide powder was obtained in the same manner as in Example 1.

[0057] Example 4 In Example 1, an alumina powder (particle size: 8.5 μm, shape: aggregated) was prepared as the second mother powder. The first mother powder and the second mother powder were mixed so that the total amount of the second mother powder contained 1.0 mass% of the first mother powder and the second mother powder to obtain a mixed mother powder, which was supplied to the DC plasma device 1. Other than this, a silicon carbide powder was obtained in the same manner as in Example 1.

[0058] Example 5 In Example 4, the first mother powder and the second mother powder were mixed so that the total of the first mother powder and the second mother powder contained 5.0 mass% of the second mother powder to obtain a mixed mother powder. Except for this, the silicon carbide powder was obtained in the same manner as in Example 4.

[0059] Example 6 In Example 4, the first mother powder and the second mother powder were mixed so that the total of the first mother powder and the second mother powder contained 10.0 mass% of the second mother powder to obtain a mixed mother powder. Except for this, the silicon carbide powder was obtained in the same manner as in Example 4.

[0060] Comparative Example 1 In Example 1, the plasma output was set to 5.0 kW so that the laminar flow state of the plasma flame was maintained at 1.0 cm. Other than this, silicon carbide powder was obtained in the same manner as in Example 1.

[0061] Comparative Example 2 As the DC plasma device, a device in which the cylindrical body 9 was removed from the DC plasma device shown in FIG. 1 was used. In Example 1, the supply amount of the first mother powder was set to 15.4 g / min. In addition, the plasma output was set to 20 kW so that the laminar flow state of the plasma flame was maintained for 15 cm. Other than this, silicon carbide powder was obtained in the same manner as in Example 1.

[0062] 〔evaluation〕 The silicon carbide powders obtained in the examples and comparative examples were evaluated for average sphericity, amount of sphericity of 0.85 or more, particle size D 50 The standard deviation SD of the particle size distribution and the BET specific surface area were calculated by the above-mentioned method. In addition, the content of silicon carbide particles having a β-type crystal structure contained in the silicon carbide powders obtained in the examples and comparative examples was calculated by the method described above. Furthermore, the green volume resistivity, green density and thermal conductivity of the silicon carbide powders obtained in the examples and comparative examples were measured by the following methods. The results are shown in Table 1.

[0063] [Powder volume resistivity and powder density] The green volume resistivity and green density were measured using a green resistance measurement system (PD-51, manufactured by Mitsubishi Chemical Analytech Co., Ltd.) and a resistivity meter (MCP-T600, manufactured by Mitsubishi Chemical Analytech Co., Ltd.). Specifically, 5 g of silicon carbide particles (sample) were first placed into a probe cylinder (φ20 mm), and the probe unit was set on the PD-51. The resistance value when a load of 20 kN was applied by a hydraulic jack was measured using the resistivity meter. The green volume resistivity (green resistance) and green density were calculated based on the measured resistance value and sample thickness.

[0064] [Thermal Conductivity] The thermal conductivity was measured under the following conditions using a laser flash thermal conductivity measuring device (device name: TC-9000 type, manufactured by ULVAC-RIKO). Sample shape: 10mm diameter x 2mm thick disc Measurement temperature: In air Measurement temperature: 25℃

[0065] [Table 1]

[0066] As is clear from the results shown in Table 1, the silicon carbide powders obtained in Examples 1 to 6 have higher pressed volume resistivity and thermal conductivity than the silicon carbide powders obtained in Comparative Examples 1 and 2, and exhibit high heat dissipation and electrical insulation properties. [Explanation of symbols]

[0067] 1 DC plasma device 2 Powder feeding device 3. Chamber 4 DC Plasma Torch 5. Collection Pot 6 Powder supply nozzle 7 Gas supply equipment 8. Pressure Regulating Device 9 Cylindrical body 10 Partition 11 Silicon carbide powder

Claims

1. A silicon carbide powder which is an aggregate of silicon carbide particles, The average sphericity is 0.70 or more, Volume cumulative particle size D at 50% cumulative volume measured by laser diffraction scattering particle size distribution measurement method 50 The silicon carbide powder has a particle size of 0.40 μm or more and 3.70 μm or less.

2. The silicon carbide particles include particles having a β-type crystal structure, The silicon carbide powder according to claim 1 , wherein the silicon carbide particles having a β-type crystal structure are contained in the silicon carbide powder in an amount of 38 mass% or more.

3. the surfaces of the silicon carbide particles are coated with alumina, silicon nitride or silica; The powder volume resistivity under 20 kN is 25.0 Ω cm or more, 3. The silicon carbide powder according to claim 1 or 2, having a thermal conductivity of 1.0 W / m·K or more in thermal conductivity measurement by a steady-state method.

4. The silicon carbide powder according to claim 3, wherein the surface of the silicon carbide particles coated with alumina, silicon nitride or silica is further coated with a dispersant.

5. A heat dissipation material comprising the silicon carbide powder according to claim 1 or 2 and a resin.

6. A method for producing silicon carbide powder, comprising the steps of supplying mother powder containing silicon carbide into a plasma flame in a laminar flow state generated in a chamber, gasifying the mother powder in the plasma flame, and cooling the gasified mother powder to generate silicon carbide particles, A method for producing a silicon carbide powder, wherein a ratio of plasma output to the supply amount of the mother powder is 0.003 kW·min / g or more and 20 kW·min / g or less.

Citation Information

Patent Citations

  • Insulating high-thermal conductivity resin composite material

    JP2010024406A